Association of maternal serum PAPP‐A levels, nuchal translucency and crown–rump length in first trimester with adverse pregnancy outcomes: retrospective cohort study. (16th June 2017) - Bilagi, Ashwini; Burke, Danielle L.; Riley, Richard D.; Mills, Ian; Kilby, Mark D.; Katie Morris, R.
Abstract : What's already known about this topic? Low levels of PAPP‐A are associated with small for gestational age and PE. What does this study adds? NT, CRL and PAPP‐A are independent prognostic markers for adverse pregnancy outcome. Further work is required to assess the predictive ability of these factors in prediction models. © 2017 John Wiley & Sons, Ltd. Abstract: Objective: Are first trimester serum pregnancy‐associated plasma protein‐A (PAPP‐A), nuchal translucency (NT) and crown–rump length (CRL) prognostic factors for adverse pregnancy outcomes? Method: Retrospective cohort, women, singleton pregnancies (UK 2011–2015). Unadjusted and multivariable logistic regression. Outcomes: small for gestational age (SGA), pre‐eclampsia (PE), preterm birth (PTB), miscarriage, stillbirth, perinatal mortality and neonatal death (NND). Results: A total of 12 592 pregnancies: 852 (6.8%) PTB, 352 (2.8%) PE, 1824 (14.5%) SGA, 73 (0.6%) miscarriages, 37(0.3%) stillbirths, 73 perinatal deaths (0.6%) and 38 (0.30%) NND. Multivariable analysis: lower odds of SGA [adjusted odds ratio (aOR) 0.88 (95% CI 0.85, 0.91)], PTB [0.92 (95%CI 0.88, 0.97)], PE [0.91 (95% CI 0.85, 0.97)] and stillbirth [0.71 (95% CI 0.52, 0.98)] as PAPP‐A increases. Lower odds of SGA [aOR 0.79 (95% CI 0.70, 0.89)] but higher odds of miscarriage [aOR 1.75 95% CI (1.12, 2.72)] as NT increases, and lower odds of stillbirth as CRL increases [aOR 0.94 95% CI (0.89, 0.99)]. Multivariable analysis of three factors together demonstrated strong associations: a) PAPP‐A, NT, CRL and SGA, b) PAPP‐A and PTB, c) PAPP‐A, CRL and PE, d) NT and miscarriage. Conclusions: Pregnancy‐associated plasma protein‐A, NT and CRL are independent prognostic factors for adverse pregnancy outcomes, particularly PAPP‐A and SGA with lower PAPP‐A associated with increased risk. © 2017 John Wiley & Sons, Ltd.